An alternative way to measure the degree of sprawl and development patterns in Austin, TX. - Lee, Hye Kyung; Kim, Hwan Yong; Kang, Sanghyeok (Area (0004-0894), 2017)
Sprawl has been named as one of the critical reasons for the latest social and urban problems in many parts of the world. This is particularly true in urban and regional planning as their main focus strategically interacts with the rise and decline of cities. A large number of studies have elaborated on the effects of sprawl and of those different perspectives on sprawl, this study focuses on a more detailed notion of the environmental aspect. The authors try to answer how to specifically estimate the ecological impact of sprawl using geographic information systems ( GIS) and ecological valuation method. With different years of land cover datasets and an ecological estimation method, the authors examine the economic losses of the Austin-Round Rock Metropolitan Statistical Area ( MSA). Based on the acreage information and median value estimates, the ecological opportunity costs are assessed to provide a comparative perspective on the amount of sprawl that occurred between 2001 and 2011. Austin's ecological stock in 2001 was $1709 million whereas in 2006 it was about $1683.6 million. In 2011, the entire ecological stock dropped to $1658.1 million making the difference approximately $25.5 million between 2011 and 2006. There can be other issues involved, such as inflated land prices or immerse influx of immigrations when explaining natural stock reduction. However, this could be regarded as one of the signs identifying the sprawl effect of a city's urban development and that should be provided as an alternative perspective on assessing plan evaluation.